2018
DOI: 10.1021/acs.inorgchem.8b00866
|View full text |Cite
|
Sign up to set email alerts
|

Th-Based Endohedral Metallofullerenes: Anomalous Metal Position and Significant Metal-Cage Covalent Interactions with the Involvement of Th 5f Orbitals

Abstract: Endohedral metallofullerenes (EMFs) containing actinides are rather intriguing due to potential 5f-orbital participation in the metal-metal or metal-cage bonding. In this work, density functional theory calculations first characterized the structure of recently synthesized ThC as Th@ D(14246)-C. We found that the thorium atom adopts an unusual off-axis position inside cage due to small metal ion size and the requirement of large coordination number, which phenomenon was further extended to other Th-based EMFs.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
43
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 25 publications
(46 citation statements)
references
References 82 publications
(147 reference statements)
2
43
0
Order By: Relevance
“…According to the mass spectra signals of Th@C 2 n (2 n = 74‐96) reported by Chen and coworkers, the possible structures of Th@D 3h (1)‐C 74 , Th@T d (2)‐C 76 , and Th@C s (10)‐C 84 are quickly proposed by our and other's theoretical calculations . Interestingly, we found that the Th atom in Th@D 3h (1)‐C 74 may undergo an unprecedented three‐dimensional motion in the cage . Besides the Th‐EMFs, Echegoyen and coworkers recently obtained three uranium metallofullerenes U@D 3h (1)‐C 74 , U@C 2 (5)‐C 82 , and U@C 2v (9)‐C 82 .…”
Section: Introductionsupporting
confidence: 66%
See 4 more Smart Citations
“…According to the mass spectra signals of Th@C 2 n (2 n = 74‐96) reported by Chen and coworkers, the possible structures of Th@D 3h (1)‐C 74 , Th@T d (2)‐C 76 , and Th@C s (10)‐C 84 are quickly proposed by our and other's theoretical calculations . Interestingly, we found that the Th atom in Th@D 3h (1)‐C 74 may undergo an unprecedented three‐dimensional motion in the cage . Besides the Th‐EMFs, Echegoyen and coworkers recently obtained three uranium metallofullerenes U@D 3h (1)‐C 74 , U@C 2 (5)‐C 82 , and U@C 2v (9)‐C 82 .…”
Section: Introductionsupporting
confidence: 66%
“…Full geometry optimizations were carried out by using the M06‐2X functional and the standard split‐valence 6‐31G* basis set for C and the Stuttgart/Dresden relativistic effective core potential and corresponding basis set for metals. The current theoretical level is denoted here as M06‐2X/6‐31G*~SDD, which has been successfully employed to study Th‐based EMFs . After optimizations, harmonic vibrational frequency analysis was then conducted at the same level of theory to identify the nature of located stationary points on the potential energy surface (PES).…”
Section: Calculation Methodsmentioning
confidence: 99%
See 3 more Smart Citations